Preminilary design of low speed wind tunnel contraction ... [et al.] / [microfilm] - 278845 Chua, Seong Khoon (Skudai : Universiti Teknologi Malaysia, 1999)
Project Paper (Bachelor of Engineering (Mechanical) - University Teknologi Malaysia,1999